Clinical Applicability of Sequence Variations in Genes Related to Drug Metabolism - Stojiljkovic, Maja; P. Patrinos, George; Pavlovic, Sonja (Current Drug Metabolism, 2011)
The Human Genome and the Hap Map Projects as well as the extensive use of deep resequencing worldwide, have contributed to a massive catalogue of reported single nucleotide polymorphisms (SNPs) and other genetic variations in the human genome. Pharmacogenomics is an emerging field that combines genetics with pharmacokinetics and pharmacodynamics of the drug in attempt to understand inter-individual differences among patients and develop more accurate drug dosing. However, only for the minority of those variations an association with phenotype has been established. Here, we provide an overview of genes and genetic variants that influence inter- individual dosing of three of the most widely used drugs, namely warfarin, irinotecan and thiopurine drugs, to highlight a tangible benefit of translating genomic knowledge into clinical practice. Therefore, particular SNPs in vitamin K epoxide reductase complex subunit 1 (VKORC1), cytochrome P450 2C9 (CYP2C9), uridine diphosphate glucoronosyltransferase 1A1 (UGT1A1) and thiopurine Smethyltransferase (TPMT) genes has proven to be applicable for optimising the dosage in pursuit of maximum efficacy and minimum adverse effects. Thus, they set an important paradigm of implementation of pharmacogenomics in the mainstream clinical practice.
Keywords: uridine diphosphate